Evaluating the California Mental Health Services Authority's Student Mental Health Initiative Year 1 Findings - Stein, Bradley D. (RAND Corporation, 2014)
California's Mental Health Services Act of 2004 mandates the state and counties to develop mental health prevention and early intervention services and education. This document summarizes first-year findings from an ongoing evaluation of one element of that program, an initiative to improve student mental health.